Kajian Hadits Tentang “Hajar Aswad” Dalam Perspektif Linguistik (Analisis Pada Matan Hadits) - Niswah MZ, Isniyatun (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2024)
Abstract— The Hadith is the second source after the Qur'an, with scholars of Hadith defining it as the sayings, actions, approvals, and all things related to the Prophet Muhammad. Historically, during the time of the Prophet, his Companions would always ask him about rulings, worship, social transactions, and all matters. However, this was no longer possible after the Prophet's death, leading to the compilation of Hadith by the Companions. In some cases, certain Hadiths reported from the Prophet cannot be immediately understood, as their texts often contain symbolic language that requires special interpretation to grasp their meaning. This research is categorized as library research. Sudaryanto outlines three stages of the research process. The first is data collection: after identifying various problems, objects, and major themes in the study, the researcher will present the data collection, including books and journals related to the research. Like other linguistic research methods, language research can follow two phases: conversation or observation. Second, data analysis is the process of organizing the data, categorizing it, and arranging it into patterns. Sudaryanto explains that analysis is the researcher’s effort to directly address the issues found in the data. Similar to data collection, data analysis can be conducted using two methods: the comparative method and the distributive method. Third, data presentation: after the data is collected and analyzed, the next step is presenting the findings. In this study, the data is presented informally, as the researcher explains the types of language used in Hadith and its relation to the historical background of the emergence of the Hadith text, using everyday language. The findings of this study conclude that the Hadith regarding the Black Stone being from paradise carries a metaphorical meaning.